Multi-channel dynamics in high harmonic generation of aligned CO2: ab initio analysis with time-dependent B-spline algebraic diagrammatic construction. Issue 12 (13th March 2018) - Ruberti, M.; Decleva, P.; Averbukh, V.
Abstract : Electron-correlation effects on the multi-channel dynamics underlying strong-field HHG response of CO2 molecule were demonstrated by ab initio ADC study. Abstract : Here we present a fully ab initio study of the high-order harmonic generation (HHG) spectrum of aligned CO2 molecules. The calculations have been performed by using the molecular time-dependent (TD) B-spline algebraic diagrammatic construction (ADC) method. We quantitatively study how the sub-cycle laser-driven multi-channel dynamics, as reflected in the position of the dynamical minimum in the HHG spectrum, is affected by the full inclusion of both correlation-driven and laser-driven dipole interchannel couplings. We calculate channel-resolved spectral intensities as well as the phase differences between contributions of the different ionization-recombination channels to the total HHG spectrum. Our results show that electron correlation effectively controls the relative contributions of the different channels to the total HHG spectrum, leading to the opening of the new ones (1 2 Πu, 1 2 Σ+g), previously disregarded for the aligned molecular setup. We conclude that inclusion of many-electron effects into the theoretical interpretation of molecular HHG spectra is essential in order to correctly extract ultrafast electron dynamics using HHG spectroscopy.